Characterization of Doped and Undoped Tin Oxide Thin Films Prepared by Sol Gel Spin Coating Technique - Kaur, Amandeep; Kumar, Rajesh (Asian Journal of Chemistry, 2017)
Optical and structural characterization of Cu-doped and pure SnO2 thin films were performed as a part of this investigation. In this respect, the effects of changing the concentration of the precursors on the thin film properties were investigated. Tin dioxide thin films both in pure and doped form were prepared by a sol gel spin coating technique. The metallic oxide (SnO2) films deposited were characterized using the UV Spectrophotometer and XRD studies. The average band gap for tin dioxide thin films was found to be approximately 3.80 eV. As far as direct band gap is concerned that copper doping appears to have no effect on the direct band gap which is in accordance with the literature. The indirect band gap for thin films was found to be approximately 3.48, 3.32 and 3.20 eV for different concentrations of the solutions, respectively. The indirect energy gap of the Cu doped thin films decreases as 3.76, 3.73 and 3.16 eV, respectively for different concentrations of the precursor solutions. The less value may be due to the addition of Cu-dopant and may also be due to growth of grain and improvement of the degree of crystallization.